(3GdEHJgGL TQM GdefgGL ddfhhis - (3Ydj Hf YHO GdcGaj Hf Ydj Hf JeGe GdSHcj GdCfUGQj GdNRQLj, CHh GdMSf, Jbqj GdOjf,J (B756 (3g` s; (3Gdfhhj,J (B676 (3g` s ((3ehSi Hf YHO Gddg GdMLGRi GdMfHdi s)
(3ChdgG (B:s
(3cJGH GdUhe s
(3BNQgG (B:s
(3aUd GdJUhjI MQGe s
(3ef GdfSNI faSgGs
(3bQf GdfSN (B:s
(3GdbQf GdKGefs
(3JHUQI GdYfhGf (B:s
(3TQMs
(3GdJhKjbGJ GdeQLYjI (B:s
Keywords: (3Gdabg GdTGaYjs